2016
DOI: 10.1007/s11150-016-9346-9
|View full text |Cite
|
Sign up to set email alerts
|

Income and child maltreatment in unmarried families: evidence from the earned income tax credit

Abstract: This study estimates the associations of income with both (self-reported) child protective services (CPS) involvement and parenting behaviors that proxy for child abuse and neglect risk among unmarried families. Our primary strategy follows the instrumental variables (IV) approach employed by Dahl and Lochner (2012), which leverages variation between states and over time in the generosity of the total state and federal Earned Income Tax Credit for which a family is eligible to identify exogenous variation in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 46 publications
4
91
0
1
Order By: Relevance
“…For example, Raissian and Bullinger (2017) show that increasing the minimum wage is associated with reductions in reports of neglect. Research has also found that an increase in the earned income tax credit is associated with a reduction in overall child maltreatment (Berger et al 2017;Klevens et al 2017). 3 These findings suggest that programs designed to increase net income for low-income families may reduce neglect by counteracting the pathways through which poverty leads to child maltreatment.…”
Section: Considerable Researchmentioning
confidence: 99%
“…For example, Raissian and Bullinger (2017) show that increasing the minimum wage is associated with reductions in reports of neglect. Research has also found that an increase in the earned income tax credit is associated with a reduction in overall child maltreatment (Berger et al 2017;Klevens et al 2017). 3 These findings suggest that programs designed to increase net income for low-income families may reduce neglect by counteracting the pathways through which poverty leads to child maltreatment.…”
Section: Considerable Researchmentioning
confidence: 99%
“…A broad literature suggests that the families most likely to be involved in the child protective services system (CPS) are poor, minority, and often single-parent families who live in low-income neighborhoods (Barth, Wildfire, & Green, 2006; Berger & Waldfogel, 2004; Berger, 2006; Berger, Font, Slack, & Waldfogel, 2013; Brandon, 2000; Courtney & Barth, 1996; Drake, Lee, & Jonson-Reid, 2009; Paxson & Waldfogel, 1999; Pelton, 1987). Such families are at greater risk of involvement with CPS and entry into foster care due to many factors, including substance abuse (Cunningham and Finlay 2013; McGuinness and Schneider 2007) and family structure instability (Berger, Paxson, & Waldfogel, 2009; Berger & Waldfogel, 2004; Paxson & Waldfogel, 2003).…”
Section: Background and Literaturementioning
confidence: 99%
“…More recently, studies have found evidence for a causal relationship between income and child maltreatment, particularly for child neglect (Berger, Font, Slack, & Waldfogel, ). They suggest that an increase in income through employment, welfare benefits, and tax credits may reduce the risk of child maltreatment (Beimers & Coulton, ; Berger et al, ). We also found that younger children were more vulnerable to resubstantiation for both cases.…”
Section: Discussionmentioning
confidence: 99%
“…Freymond and Cameron (2006) have even stated that living in poverty is "the most consistent and strongest statistical predictor of having an open child protection case" (p.11). More recently, studies have found evidence for a causal relationship between income and child maltreatment, particularly for child neglect (Berger, Font, Slack, & Waldfogel, 2017). They suggest that an increase in income through employment, welfare benefits, and tax credits may reduce the risk of child maltreatment (Beimers & Coulton, 2011;Berger et al, 2017).…”
Section: Discussionmentioning
confidence: 99%